Learning From Love Island? Diversification of the Hegemonic Man - Nichols, Kitty (Frontiers in Sociology, 2019)
It is undeniable that Love Island promotes specific ideas of masculinity and masculine behaviors. There is an “expected” masculinity performed in the villa, exemplified in cases, such as “The Do Bits Society” which advocates heteronormative forms of masculinity and gender relations (Whitehead and Barrett, 2008). Within such examples men had to successfully perform what Schrock and Schwalbe (2009) refer to as “manhood acts” in order to prove their masculine identity. This form of masculinity, which dominated the space, can be explained sociologically via intersecting hegemonic and performance theorizing (Goffman, 1974; Connell, 2005; Butler, 2008; Wellard, 2009). However, utilizing new combinations of theoretical approaches, this paper will explore more diverse performances of masculinity present in the villa. This includes the ways that men were making choices in the construction of their masculine identities beyond the “expected” masculinity which dominated, as well as how women also performed this form of masculinity. Through analysis of two seasons of Love Island (2018 and 2017), this paper will highlight how lines between different ways of living and experiencing masculinity can be blurred and fluid. In doing so, the paper encourages a critique of how we theorize masculinity and gender more widely, allowing for emergent theorizing which blends existing theories in new ways.